Physicochemical properties of polymers: An important system to overcome the cell barriers in gene transfection. Issue 7 (July 2015) - Namvar, Ali; Bolhassani, Azam; Khairkhah, Niloofardokht; Motevalli, Fatemeh; Case, David
ABSTRACT Delivery of the macromolecules including DNA, miRNA, and antisense oligonucleotides is typically mediated by carriers due to the large size and negative charge. Different physical (e.g., gene gun or electroporation), and chemical (e.g., cationic polymer or lipid) vectors have been already used to improve the efficiency of gene transfer. Polymer‐based DNA delivery systems have attracted special interest, in particular via intravenous injection with many intra‐ and extracellular barriers. The recent progress has shown that stimuli‐responsive polymers entitled as multifunctional nucleic acid vehicles can act to target specific cells. These nonviral carriers are classified by the type of stimulus including reduction potential, pH, and temperature. Generally, the physicochemical characterization of DNA‐polymer complexes is critical to enhance the transfection potency via protection of DNA from nuclease digestion, endosomal escape, and nuclear localization. The successful clinical applications will depend on an exact insight of barriers in gene delivery and development of carriers overcoming these barriers. Consequently, improvement of novel cationic polymers with low toxicity and effective for biomedical use has attracted a great attention in gene therapy. This article summarizes the main physicochemical and biological properties of polyplexes describing their gene transfection behavior, in vitro and in vivo. In this line, the relative efficiencies of various cationic polymers are compared. © 2015 Wiley Periodicals, Inc. Biopolymers 103: 363–375, 2015.